1977
DOI: 10.1128/aem.33.2.485-487.1977
|View full text |Cite
|
Sign up to set email alerts
|

Plating Medium for Differentiating Salmonella arizonae from Other Salmonellae

Abstract: A differential plating medium developed for isolation of Salmonella arizonae produces a uniform reaction for both lactose-negative and -positive S. arizonae and differentiates S. arizonae from other salmonellae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Arizona colonies on BS agar have been reported as looking like typical Salmonella spp. colonies (13,16); however, like Greenfield et al (10), we found Arizona colonies on BS to be coliform-like, being olive green with darker centers. In addition, one strain of Arizona sp.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Arizona colonies on BS agar have been reported as looking like typical Salmonella spp. colonies (13,16); however, like Greenfield et al (10), we found Arizona colonies on BS to be coliform-like, being olive green with darker centers. In addition, one strain of Arizona sp.…”
Section: Discussionsupporting
confidence: 73%
“…Reliance on such differentiation can be a problem in detecting salmonellae under certain instances where (i) the high acidity produced by the background colonies can mask the differential reaction of Salmonella colonies (18), and (ii) certain strains of salmonellae are able to utilize these sugars and subsequently resemble the background coliform organisms (2,10,16,18,20). These conditions can mean missed opportunities for isolating members of this genus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations